Feedback from central massive black holes in galaxies using cosmological simulations. Issue Volume 15:Issue S359(2020) (March 2019) - Barai, Paramita
Abstract: Gas accretion onto central supermassive black holes of active galaxies and resulting energy feedback, is an important component of galaxy evolution, whose details are still unknown especially at early cosmic epochs. We investigate BH growth and feedback in quasar-host galaxies at z ⩾ 6 by performing cosmological hydrodynamical simulations. We simulate the 2 R 200 region around a 2 × 10 12 M ʘ halo at z = 6, inside a (500 Mpc) 3 comoving volume, using the zoom-in technique. We find that BHs accrete gas at the Eddington rate over z = 9–6. At z = 6, our most-massive BH has grown to M BH = 4 × 10 9 Mʘ . Star-formation is quenched over z = 8–6.